WATER FOR LIFE: CONTAMINATION, VULNERABILITY AND SOCIAL DETERMINANTS IN PERIPHERAL TERRITORIES OF EUNÁPOLIS AND PORTO SEGURO - Almeida da Silva, Flaelma; Eduarda Queiroz Cerqueira, Maria; Nirvana Souza Cajado, Lainara; Miguel Medeiros Martins, Pedro; Carenina de Oliveira Andrade, Larissa; Victor Queiroz de Oliveira, Kaio; Melo Marques, Aiça (Health and Society, 2025)
Water insecurity in peripheral territories, settlements, and traditional villages represents a persistent challenge to the guarantee of the human right to water and to public health. This study, developed as part of a scientific extension initiation project, aimed to evaluate the quality of water intended for human consumption at twelve points located in rural and Indigenous communities in the municipalities of Eunápolis and Porto Seguro, Bahia. The objective was not only to identify the level of contamination but also to understand the social and environmental determinants that shape sanitary risks in these contexts. This is an observational, cross-sectional study with a quantitative and qualitative approach. Data were obtained through physicochemical and microbiological analyses of water, in accordance with the parameters established by Ordinance GM/MS No. 888/2021, and through structured interviews conducted with residents of the territories. The samples revealed a high presence of total and fecal coliforms in most of the investigated points, as well as nonconformities in pH, turbidity, residual chlorine, consumed oxygen, and alkalinity. The interviews revealed the absence of sanitation infrastructure, inadequate water storage and treatment practices, and a low perception of sanitary risk. The findings highlight the interrelationship between precarious socio-environmental conditions and the prolonged exposure of populations to waterborne diseases, reinforcing the need for integrated interventions in sanitation, environmental surveillance, and health education.